STUDENTS’ MATHEMATICAL REASONING ABILITY AS AN OUTCOME OF THE CREATIVE PROBLEM SOLVING (CPS) LEARNING MODEL - Zahro, Ayu Naharotu; Nurhanurawati, Nurhanurawati; Rumite, Wayan (Jurnal Pendidikan Matematika dan IPA, 2026)
Mathematical reasoning does not grow from memorization, but from the experience of solving real problems that encourage students to think logically, make connections between concepts, and make decisions based on deep understanding. To find out the results of students' mathematical reasoning skills through the creative problem solving (CPS) learning model. Sampling in this study was conducted using cluster random sampling, research was conducted using a mixed method. The subjects in this study were 32 students of class VIII B of SMP Muhammadiyah 3 Bandar Lampung. The purpose of this study was to determine the effect of using the CPS model on students' mathematical reasoning abilities. Quantitative data were analyzed using the normalized gain value (N-Gain) to measure the improvement of students' mathematical reasoning ability then the Mann-Whitney U test was used. Qualitative data were analyzed through data reduction, data presentation, and conclusion drawing stages. The results showed that the CPS learning model can improve students' mathematical reasoning ability. These results are supported by the results of interviews which show that the increase is due to students being able to understand the problems in the test instrument.